Investigating the Awareness and Attitude of Medical Personnel of two referal Hospitals about Diseases Leading to the Dissolution of Marriage - Najari, Fares; Najari, Dorsa; Fazleh Hashemi, Rana (Archives of Men’s Health, 2023)
Background: A criterion for the right termination of marriage is a disadvantage of the spouse, which burdens the other party. To solve this problem, defects are considered for couples in jurisprudence and law, and if they are incurable, the marriage contract is terminated. In this study, we examined the awareness and attitude of medical personnel about this issue. Methods: In this descriptive-analytical study, which was done in the first half of 2021, the personnel of Shohada Tajrish and Shahid Modares hospitals were evaluated using a researcher-made data collection form. The effects of demographic factors (age, sex, marriage, and education) were also investigated. Sampling was done by census method and employed according to the inclusion criteria. Cochran’s formula was used to calculate the minimum sample size. Fisher and Pearson’s statistical tests in SPSS21 software were used for data analysis. Results: The knowledge and awareness of the participants in all age groups under the study was similar (P>0.2). All participants were aware of insanity as an obstacle to marriage and were unaware of other diseases leading to marriage termination. After learning that 10 to 11 diseases caused the annulment of marriage, they added all the incurable diseases to this list, and they had a negative attitude towards these restrictions. Conclusion: Most medical personnel had little awareness about the number of marriage annulment cases. There was a negative attitude toward discrimination between men and women in the number of these diseases.